Reformation und Recht Ein Beitrag zur Kontroverse um die Kulturwirkungen der Reformation - Strohm, Christoph (Mohr Siebeck, 2017)
The law's cultural and especially its religious contexts present a fresh challenge to a globalised world. Did the Reformation's demand for the abolition of canonical law have particular consequences for legal development? Various answers are given to this question. It has been the objective of recent confessionalization research to highlight the uniformity of confessions and their cultural effects. There is great concern that, as happened a hundred years ago, Protestantism is once again being awarded a special proximity to modernity. The authors of this volume discuss the consequences the Reformation had for the development of various branches of the law. In the sense of a comparative analysis, Catholic law is also investigated for the connection between law and morality.